A core-skirt designed artificial cornea with orthogonal microfiber grid scaffold. (June 2020) - Wang, Jieqiong; Chen, Yun; Bai, Ying; Quan, Daping; Wang, Zhichong; Xiong, Liming; Shao, Zengwu; Sun, Wei; Mi, Shengli
Abstract: Artificial cornea is an effective treatment option for cases of severe corneal loss. In this study, we prepared a core-skirt designed artificial cornea with orthogonal microfiber grid scaffold. We fabricated PCL orthogonal microfiber grid scaffolds by a direct writing technique, and then combined them with compressed collagen (CC) to obtain a sandwich-like CC/P (where P is used to represent the PCL microfiber grid scaffold). PHEMA hydrogel and the CC/P served as the core and the skirt, respectively, with the P also serving as an intermediate between the two. The physical properties of the artificial cornea, including the morphology, the mechanical properties and the light transmittance, were evaluated. SEM images showed an effective connection and a lack of phase separation at the interface between the core and the skirt, and the skirt formed a highly porous scaffold that promoted tissue biointegration. In addition, we used the skirt structure to construct a corneal tissue model containing two cells types: corneal stromal stem cells (CSSCs) and mouse hippocampal neurons. The results showed that the cells could grow and differentiate well, and the orthogonal microfiber grid scaffold fibers were good guides for the structural growth of CSSCs and neuronal axons. Highlights: Preparation of orthogonal microfiber grid scaffold by direct writing technology. A new core-skirt artificial cornea in which microfiber grid scaffolds act as a connection between the core and the skirt. Constructed a 3D co-culture model of corneal stromal cells and neurons.